Think globally act locally: the case for symphysiotomy. - Douwe Arie Anne Verkuyl (PLoS Medicine, 2007)
When expatriate doctors from developed countries working in sub-Saharan Africa suggest to the local doctors and midwives that symphysiotomies should sometimes be done, they are silenced neither with quotations from the medical literature nor with tales of patients seen, but with: "If symphysiotomies are such good operations why don't you perform them at home?" Here is why.